Green manures for maize-bean systems in eastern Uganda: Agronomic performance and farmers' perceptions - Fischler, MA; Wortmann, Charles S. (Springer, 1999)
Researchers worked with farmers in eastern Uganda to develop alternatives for soil management using crotalaria (Crotalaria ochroleuca), mucuna (Mucuna pruriens var. utilis), lablab (Dolichos lablab), and canavalia (Canavalia ensiformis) as green manures in short-term fallows. The participatory research was part of a community-based approach for systems improvement. Grain yields of maize (Zea mays) and bean (Phaseolus vulgaris) following one season of crotalaria fallow were 41% and 43%, respectively, more than following a two-season weedy fallow. Grain yields of maize following a one-season fallow with mucuna and lablab were 60% and 50% higher, respectively, as compared with maize following maize. Maize and bean yield were more, although effects were small, during the second and third subsequent seasons, indicating probable residual effects of the green manures. Mucuna and lablab were successfully produced by intersowing into maize at three weeks after sowing maize, although the yields of the associated maize crop were reduced by 24% to 28%. Farmers estimated the labor requirements for mucuna and lablab to be less than for crotalaria. Farmers independently experimented on how these species can be integrated into banana (Musa spp.), coffee (Coffea robusta), sweet potato (Ipomoea batatas), and cassava (Manihot esculenta) production systems. Farmers reported that the beneficial effects of the green manures included higher food-crop yields; weed suppression; improved soil fertility, soil moisture, and soil tilth; and erosion control. Mucuna and lablab were preferred because of reduced labor requirements and increased net benefits compared with continuous cropping. Farmer participation in the green manure research resulted in efficient generation and adaptation of green manure technology now being promoted in eastern and central Uganda.